Public Perceptions on the Procedural Values and Proposed Outcomes of the Finnish Climate Change Act Amendment - Albrecht, Eerika; Pietilä, Iikka; Saarela, Sanna-Riikka (Frontiers in Climate, 2022)
This article examines the public perceptions on the drafting process of Finnish Climate Act amendment, which is a legislation on the climate policy that aims to mitigate climate change and secure adaptive capacity. In this paper we present results of a thematic analysis, which reveals citizens’ perceptions of the procedural values, with respect to transparency, participation, and acceptance, and the objectives of the amendment, such as the climate neutrality target for 2035. The research data consisted of 2,458 answers to a citizen survey on the Finnish Climate Change Act amendment. Our results reveal that the opinions of citizens ranged from highlighting the urgency of political action to climate denials, with varying perceptions on process and proposed outcomes. While over half of citizens felt positively about the 2035 climate neutrality target created in the Climate Change Amendment Act, only a third believed that there was appropriate opportunity for public participation in the amendment process. Based on these findings, we suggest that participatory and transparent processes in legislative drafting are prerequisites for the sustainability transition and the implementation of international climate mitigation targets.